The impacts of international exchange programs on Moroccan teachers’ professional development: the case of in- presence programs - Oubit, Sidi Mohamed; El Farahi, Abdellatif (Frontiers in Education, 2024)
During the last decades, many Moroccan TEFL teachers have participated in different international exchange programs. Although much attention has been paid to such programs globally, there is no study that assesses the impact nationally. The actual study aims to explore the benefits of such programs on Moroccan TEFL teachers’ personal and professional development. It surveys their attitudes, knowledge and practices after they participate. This includes language awareness, techniques and strategies in teaching, leadership, soft skills and cultural competence. The results of the study prove that exchange programs promote the development of teachers’ personal, professional and intercultural competencies, namely language acquisition, intercultural understanding, easy integration in unfamiliar contexts, and efficiency in teaching. Thereafter, it in the end gives some recommendations to different partners in the educative sector in order to encourage this type of programs.